2003
DOI: 10.1002/hon.716
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of acute graft‐versus‐host disease

Abstract: Graft-versus-host disease (GVHD) has been the primary limitation to the wider application of allogeneic bone marrow transplantation (BMT). The pathophysiology of acute GVHD is complex and can be conceptualized to be a three-step process based on murine studies. In step 1, the conditioning regimen leads to the damage and activation of host tissues and induces the secretion of inflammatory cytokines. As a consequence, the expression of MHC antigens and adhesion molecules is increased enhancing the recognition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
110
0
10

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 150 publications
(123 citation statements)
references
References 131 publications
(141 reference statements)
3
110
0
10
Order By: Relevance
“…Human acute GVHD is believed to occur in 3 phases: (phase 1) recipient conditioning, (phase 2) donor T cell activation, and (phase 3) effector cells mediating GVHD [49]. In this study, we found evidence that all three of these phases were replicated in the development of lethal X-GVHD in NOD/SCID-β2m null mice injected with huT cells.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…Human acute GVHD is believed to occur in 3 phases: (phase 1) recipient conditioning, (phase 2) donor T cell activation, and (phase 3) effector cells mediating GVHD [49]. In this study, we found evidence that all three of these phases were replicated in the development of lethal X-GVHD in NOD/SCID-β2m null mice injected with huT cells.…”
Section: Discussionmentioning
confidence: 56%
“…Studies in both humans and animals have demonstrated that acute GVHD is closely associated with the intensity and toxicity of the recipient conditioning regimen [49]. In this study, we found that TBI (phase 1) was essential to consistently induce lethal acute X-GVHD in NOD/ SCID-β2m null recipients injected with huT cells.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations